Evaluation of 55 Cases with Spondylodiscitis Due to Brucellosis - Servet KÖLGELİER; Nazlım AKTUĞ DEMİR; Aykut AKPINAR; Serap ÖZÇİMEN; Lütfi Saltuk DEMİR; Adem YILDIRIM; Şua SÜMER (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: The aim of this study was to evaluate the demographic, clinical, and laboratory findings of 55 cases diagnosed as spondylodiscitis due to brucellosis. Materials and Methods: This study was performed between 1 January 2010 and 31 December 2011. It included patients over 18 years of age who were diagnosed as spondylodiscitis by neurosurgery and physical medicine and rehabilitation specialists in the presence of clinical findings (a titer ≥1/160 in standard tube agglutination (STA) and/or growth of Brucella spp. in appropriately obtained cultures) in addition to magnetic resonance imaging (MRI) findings. Patient charts, which included age, sex, laboratory culture results, treatment protocols, and radiographic findings, were evaluated retrospectively. Data were recorded to the SPSS 16.0 package program, and descriptive statistics and Mann-Whitney U tests were used. A p value <0.05 was considered statistically significant. Results: Thirty-two (58.2%) patients were male and 23 (41.8%) were female. The most common three findings were lower back pain (100%), fever (83.6%) and night sweats (81.8%). Lumbar vertebra involvement was detected in 50 patients, thoracal vertebra involvement in 4 and cervical vertebra involvement in 1. Multiple discs were involved in 17 patients. When we evaluated patients according to gender, fatigue was more frequent in females (p=0.046), the mean age of males was higher (p=0.018), and multiple disc involvement was more frequent in males (p=0.04). The most frequently involved vertebrae were L4-5. Follow-up MRIs of 36 patients could be obtained at the 12th week of treatment. Inflammation and edema in the disc space had increased in 6 (16.6%), decreased in 20 (55.6%), and were unchanged in 10 (27.8%) patients. Conclusion: Spondylodiscitis can be observed as a result of musculoskeletal involvement, which is the most common complication of brucellosis, and the lumbar region is the most frequently affected. In spinal brucellosis, first the vertebra corpus is involved, then spread to the neighboring disc space and vertebra corpus is observed, and with disc involvement, spondylitis evolves into spondylodiscitis. Brucellosis should be considered in the differential diagnosis in the presence of fever and lower back symptoms, especially in patients living in endemic regions.